Mediterranean Diet: What Are the Consequences for Menopause? - Vetrani, Claudia; Barrea, Luigi; Rispoli, Rosa; Verde, Ludovica; De Alteriis, Giulia; Docimo, Annamaria; Auriemma, Renata Simona; Colao, Annamaria; Savastano, Silvia; Muscogiuri, Giovanna (Frontiers in Endocrinology, 2022)
Menopause is a natural event occurring in woman’s life that is often accompanied by symptoms that might affect the quality of life. Diet has been shown to influence menopausal-related symptoms. Therefore, the present study aimed to investigate whether the adherence to the Mediterranean Diet (MD) might influence menopausal symptoms in women with obesity. This cross-sectional study involved postmenopausal women with obesity. Anthropometric and clinical parameters, and lifestyle habits were evaluated. All participants underwent interview questionnaires to assess: the adherence to the MD (PREDI PREvencion con DIetaMEDiterranea, PREDIMED), sleep quality (Pittsburgh Sleep Quality Index, PSQI), and severity of menopausal symptoms (Menopausal Rating Scale, MRS). One-hundred postmenopausal women were enrolled (age 57.1±7.3 years, BMI 35.0±5.5 kg/m2). The mean PREDIMED score was 7.82±1.66 showing moderate adherence to MD. Women in the marked MRS class had a significant lower PREDIMED score than none-to-moderate MRS class (p=0.036). The intake of legumes was associated with a lower MRS class (r= -0.201, p=0.045). In addition, the intake of extra virgin olive oil inversely correlated with psychological symptoms (r= -0.230 p=0.021). Finally, 79% of participants were poor sleepers (mean PSQI score was 8.68±3.6) and women in the severe MRS class had a worse sleep quality compared to other MRS classes. Post-menopausal women with marked menopausal symptoms had low adherence to MD. Legume consumption associated to lower menopausal symptoms severity while extra virgin olive oil consumption was associated with lower psychological symptoms.